THE CORRELATIONS AMONG COMPONENTS OF METABOLIC SYNDROME PSA AND PROSTATE VOLUME IN BPH PATIENTS - Sumasta, Yanuar Wicaksana; Danarto, Danarto (Indonesian Urological Association, 2016)
Objective: This study was to evaluate the associations among metabolic components, prostate specific antigen (PSA), and prostate volume (PV) in benign prostate hyperplasia (BPH) patients.Material & method: During the period from January 1, 2010 to August 31, 2013, 61 mens were diagnosed with BPH were enrolled. PV by transabdominal ultrasonography of the prostate, serum PSA, metabolic syndrome (MS) related parameters were investigated. MS was defined according to the modified National Cholesterol Education Program Third Adult Treatment Panel Guidelines. We evaluated the correlation between PSA, PV and MS components using Spearman’s test and Independent t test.Results: PV were not correlated with MS criteria (p=0.591) PSA total also were not correlated with MS criteria (p=0.305). PV were not correlated with each components MS; cholesterol total (p=0.593), trigliserid (p=0.479), HDL (p=0.702), LDL (p=0.512), blood glucose (p=0.317). PSA total were not correlated with each components MS; cholesterol total (p=0.255), trigliserid (p=0.543), HDL (p=0.446), LDL (p=0.615), blood glucose (p=0.987). Conclusion: There were no associations among metabolic syndrome criteria and each components, prostate volume and PSA total.